Public-Private Partnerships in the Electric Vehicle Charging Infrastructure in China: An Illustrative Case Study - Kun Wang; Yongjian Ke (Advances in Civil Engineering)
Effective supply of charging infrastructure is a necessary support for the development of electric vehicle and also an important strategic measure to promote energy consumption revolution and green development. The construction and operation of charging infrastructure in China is unfortunately not smooth, lagging behind the actual demand. Public-Private Partnerships (PPPs) may offer a promising way forward and accelerate the development of charging infrastructure by tapping the private sectors’ financial resources and professional skills. However, PPP has not been commonly adopted in this sector yet. This paper hence studied an illustrative case of Anqing Project in China to demonstrate how governments structure a PPP deal in the electric vehicle charging infrastructures. A content analysis was conducted on the important project documents to investigate key elements including the planning, construction, risk sharing, profit distribution, and supervision during the execution stage. Based on the illustration, some key lessons and recommendations were provided to offer a reference for future charging infrastructure PPP projects in China.